2015
DOI: 10.1108/pr-04-2013-0061
|View full text |Cite
|
Sign up to set email alerts
|

Psychological contract breach, organizational justice and emotional well-being

Abstract: Purpose – Psychological contract breach, which represents instances when organizations fail to fulfil their side of the employment bargain, has been associated with salient concepts in strategic human resources management. The purpose of this paper is to investigate moderated mediated relationships involving breach, organizational (procedural and interactional) justice and emotional well-being. Design/methodology/approach – The study dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 80 publications
5
58
0
1
Order By: Relevance
“…Emotion is mediating the relationship between perceieved organizational justice and revenge act. Cassar and Buttigieg (2015) found that violation in psychological contract breach is mediating the relationship organizational justice and emotion. Dzansi (2016) demonstrated that perceived organizational justice concerning human resource management in the workplace is affecting the quality of service rendered by the employees.…”
Section: Organizational Justice and Emotionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotion is mediating the relationship between perceieved organizational justice and revenge act. Cassar and Buttigieg (2015) found that violation in psychological contract breach is mediating the relationship organizational justice and emotion. Dzansi (2016) demonstrated that perceived organizational justice concerning human resource management in the workplace is affecting the quality of service rendered by the employees.…”
Section: Organizational Justice and Emotionmentioning
confidence: 99%
“…They will feel that they receive appropriate appreciation and satisfaction from playing part in organization's goals achievement. The satisfaction acquired is a positive emotional form from the achievement of perceived values related with their job and these values are in line with their needs (Cassar & Buttigieg, 2015). Moreover, we could say that positive emotion will impact civil servants job satisfaction as proposed by Barclay and Skarlicki (2009).…”
Section: Introductionmentioning
confidence: 96%
“…Breach of the psychological contract involves a perception that the company has reneged on the obligations that it promised to fulfil (Cassar & Buttigieg, 2015;Piccoli & De Witte, 2015). Perceived fulfilment or psychological contractual obligations influence employee attitudes and behaviours such as job satisfaction and perceived job security (Ahmed, D'Netto, Chelliah & Fein, 2016;Payne, Culbertson, Lopez, Boswell & Barger, 2015), organisational citizenship behaviours, turnover intentions and actual turnover (Bauer & Matzler, 2014) and motivation and performance (Weber & Fried, 2011).…”
Section: The Psychological Contractmentioning
confidence: 99%
“…Despite its importance in achieving organization priorities, only 27% of those who work in HRM are actually trained in the field and fail to understand the complex purposes and roles of HRM (Cassar, V., Buttgieg, S. C., 2015). In many organizations, the role of HRM is considered to be a financial control function to limit the expenses of HRM as a cost center.…”
Section: The Hrm Rolesmentioning
confidence: 99%